ANALISIS KUALITAS LAYANAN SISTEM INFORMASI AKADEMIK SMAN 1 TANGERANG SELATAN TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN FRAMEWORK WEBQUAL 4.0 DAN IPA - Ditha Nadhira Jasmine (2023)
The development of technology is very fast and rapid, where the use of websites is also growing among educational institutions supported by the Covid-19 pandemic. SMAN 1 South Tangerang uses the website in carrying out its learning and teaching activities. Evaluation of the SIAKAD website used needs to be done to find out the problems to improve the quality of the website. Webqual 4.0 which has 3 dimensions, namely usability, information quality, and service interaction quality is a method to assess the service quality of the SKMS SMAN 1 South Tangerang website. Researchers conduct a type of quantitative research using research instruments in the form of questionnaires, where respondents are determined using proportional stratified random sampling techniques. From the existing data based on actual assessments and user expectations, researchers look for gap analysis, webqual index (WQI) values, and Importance Performance Analysis (IPA) values. The results of this study are in the form of website quality scores of 0.80 or very good overall and indicators in quadrant I, namely US_1, US_3, US_5, US_8, SQ_2, SQ_6, and SQ_7 which are the focus of improvement by including user interface recommendations.